2001
DOI: 10.1016/s0378-1097(01)00178-1
|View full text |Cite
|
Sign up to set email alerts
|

The molecular mechanisms of conidial germination

Abstract: The asexual spore, or conidium, is critical in the life cycle of many fungi because it is the primary means for dispersion and serves as a`safe house' for the fungal genome in adverse environmental conditions. This review discusses the physiological process of germination, conidial adhesion and initiation of protein synthesis and also the regulatory pathways used to activate conidial germination. These include Ca 2 / calmodulin-mediated signaling, the cyclic AMP/protein kinase A and the ras/mitogen-activated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 45 publications
2
52
0
2
Order By: Relevance
“…In Candida albicans, it has been related to primary resistance to flucytosine, an antifungal reagent (Hope et al 2004), which may indicate a role of the pyrimidine "de novo" synthesis as a therapeutic target for fungicide design and the development of fungal virulence. The correlation of early stages of conidial germination with the accumulation of proteins related to translation has been reported in previous studies for different filamentous fungi as N. crassa, A. nidulans and F. solani (Osherov and May 2001). These studies are consistent with our results since we have identified a set of proteins related to protein translation, which were overaccumulated in germinated conidia, such as (1) ribosomal proteins, e.g., phosphoribosylaminoimidazole carboxylase (spots 18), nucleolar protein 13 (spot 58) and (2) a considerable amount of elongation and translational initiation factors like elongation factors eEF-3 (spots 2, 3, 4, 5) and 1-gamma 1 (spot 32), the translation elongation factor EF-Tu (spot 40) and elongation factor 1-alpha (spot 47), the translational initiation factor 4E−2 (spot 57 and 59), as well as (3) heat shock proteins (spot 7, 8, 9, 10, 11 and 48) (see Table 1), which are functionally linked to translation elongation factors and ribosomal proteins to maintain the integrity of the folding confirmation of nascent polypeptides (Cooper et al 2007).…”
Section: Proteome Miningsupporting
confidence: 73%
See 1 more Smart Citation
“…In Candida albicans, it has been related to primary resistance to flucytosine, an antifungal reagent (Hope et al 2004), which may indicate a role of the pyrimidine "de novo" synthesis as a therapeutic target for fungicide design and the development of fungal virulence. The correlation of early stages of conidial germination with the accumulation of proteins related to translation has been reported in previous studies for different filamentous fungi as N. crassa, A. nidulans and F. solani (Osherov and May 2001). These studies are consistent with our results since we have identified a set of proteins related to protein translation, which were overaccumulated in germinated conidia, such as (1) ribosomal proteins, e.g., phosphoribosylaminoimidazole carboxylase (spots 18), nucleolar protein 13 (spot 58) and (2) a considerable amount of elongation and translational initiation factors like elongation factors eEF-3 (spots 2, 3, 4, 5) and 1-gamma 1 (spot 32), the translation elongation factor EF-Tu (spot 40) and elongation factor 1-alpha (spot 47), the translational initiation factor 4E−2 (spot 57 and 59), as well as (3) heat shock proteins (spot 7, 8, 9, 10, 11 and 48) (see Table 1), which are functionally linked to translation elongation factors and ribosomal proteins to maintain the integrity of the folding confirmation of nascent polypeptides (Cooper et al 2007).…”
Section: Proteome Miningsupporting
confidence: 73%
“…condition (Leroch et al 2013).Conidial germination is a very complex and varied process depending on the fungal specie, in which several morphological and biological changes occur during the first hours. These changes generally include swelling of conidia, adhesion, increasing intracellular osmotic pressure, uptake of water (Taubitz et al 2007) and nuclear decondensation during the first hours of germination (Osherov and May 2001;Oh et al 2010). Because its relevant role in the establishment of the fungal disease, the germination process has been widely studied; (Oh et al 2010;Cooper et al 2007;Taubitz et al 2007;Hagag et al 2012;Leroch et al 2013).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Also, a pre-existing mRNA pool has been reported to occur in dormant spores along with the enzymatic machinery that is quickly activated upon spore germination, allowing nutrient transport into the spores (Osherov and May 2001). EST sequences from spores of filamentous fungi suggest that RNA storage takes place during basidiosporogenesis and is intended to direct spore germination and initial germ tube growth (Thomas et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In A. nidulans, morphogenetic landmarks have been correlated with the duplication cycle and a stepwise growth pattern has been characterized (Harris, 1997;Momany and Taylor, 2000). A conidium breaks dormancy when it contacts appropriate signals from the environment (Osherov and May, 2001). The conidium initially expands isotropically, but soon switches to polar growth.…”
Section: Introductionmentioning
confidence: 99%